Dos cartas, dos informantes, dos tradiciones - Castillo Sánchez, Wellington (2018)
The present work deals with the search, discovery and exhibition of two letters written to Palma by two informants from the city of Huamachuco, Nicolás Rebaza Cueto and Francisco Moreno Azcate, whose texts include the written source of the Traditions “The witches of Shulcahuanga”, and the third part of “The burial seekers”. The exegesis is done to the literary texts of both traditions confirming the findings of the studies and extensive criticism that has been made to the life and work of the Patriarch of our letters, and, in the case of “The witches of Shulcahuanga”, in the reaches of the critique, many different conclusions to which some authors have arrived, achieving more, the objectives of the meetings denominated “Re-vision of the Traditions”.